(untitled) (Perner’s Contacts, 2011)
The long term objective in the field of urban mobility is an effort to prioritize public transport before individual transport. One option to fulfill this goal is to increase the attractiveness of public transport from the perspective of their users - passengers. Existing passengers can keep improving service quality in public transport. Means of improving quality in public transport are now telematics systems, which offer passengers a range of services.